Comparison of enzyme immunoassay, latex agglutination and polyacrylamide gel electrophoresis for diagnosis of rotavirus in children. Issue 1 (1st January 2020) - El-Ageery, Safaa Mohamad; Ali, Rabab; Abou El-Khier, Noha Tharwat; Rakha, Shirien Amin; Zeid, Mayada Sabry
ABSTRACT: Rotavirus is considered an important pathogen that causes diarrhea in children. Its laboratory identification is critical for early management and prevention of the outbreak. The aim of this study was to compare the three assays designed for diagnosis of rotavirus in stool samples: polyacrylamide gel electrophoresis (PAGE) as gold standard method, with the antigen detection method using enzyme immunoassay (EIA) and latex agglutination (LA). A cross-sectional retrospective study included 200 stool samples collected from children aged over 5 years with acute gastroenteritis. PAGE, EIA and LA techniques were used for the detection of rotavirus. LA showed higher percentage (36.5%), while EIA and PAGE were nearly equal (32% and 31.5%, respectively) in detection of rotavirus. Compared to PAGE, EIA presented 92.06%, 96.35%, 92.18 and 97.05 of sensitivity, specificity, positive and negative predictive values, respectively. The sensitivity, specificity, positive and negative predictive values of LA test were 84.13%, 85.40%, 72.60% and 92.12%, respectively. Antigen detection using EIA is sensitive, specific and rapid technique for detection of rotavirus infection in stool, while LA may be useful in disease outbreak, or with shortage of means for rotavirus recognition, since it is practical, fast, and reasonably priced.